Post Cesarean Section Peritonitis: A Case Report of Ogilvie's Syndrome - Mahdi Saberi Pirouz; Ali Tayebi; Fatemeh Sheibani; Faranak Olamaeian (Clinical Case Reports, 2025)
ABSTRACT Acute colonic pseudo‐obstruction (ACPO) is characterized by colon dilation without a mechanical obstruction. This report describes a 39‐year‐old pregnant woman who developed ACPO following a cesarean section. Right hemicolectomy, distal ileoctomy, and enterorraphy, with subsequent ileostomy and colostomy mucus fistula placement were done. Early consideration of the disease and its diagnosis is crucial for initiating treatment instantly to maximize the benefits of non‐invasive medications and minimize the need for surgical procedures and potentially life‐threatening complications following a cesarean section.